2017
DOI: 10.1002/asna.201713402
|View full text |Cite
|
Sign up to set email alerts
|

A search for spectral variability in the highly magnetized O9.7 V star HD 54879

Abstract: The O9.7 V star HD 54879 possesses the second strongest magnetic field among the single, magnetic, O‐type stars. In contrast to other magnetic O‐type stars, the chemical abundance analysis of HD 54879 indicated a rather normal optical spectrum without obvious element enhancements or depletions. Furthermore, spectral variability was detected only in lines partly formed in the magnetosphere. As this star shows such a deviate, almost nonvariable, spectral behavior, we performed a deeper analysis of its spectral v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…12, we display the strongest Zeeman feature identified in our spectra, which is related to an unidentified emission line with an unknown Landé factor at a wavelength close to 5220.45 Å. If this feature is real, then the inferred longitudinal magnetic field would have positive polarity, which would be inconsistent with the negative polarity measured from the absorption lines ( Bz = −578 ± 21 G; Järvinen et al 2017). Obviously, high-resolution spectra obtained at higher S/N are necessary to investigate in detail the emitting regions in HD 54879.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…12, we display the strongest Zeeman feature identified in our spectra, which is related to an unidentified emission line with an unknown Landé factor at a wavelength close to 5220.45 Å. If this feature is real, then the inferred longitudinal magnetic field would have positive polarity, which would be inconsistent with the negative polarity measured from the absorption lines ( Bz = −578 ± 21 G; Järvinen et al 2017). Obviously, high-resolution spectra obtained at higher S/N are necessary to investigate in detail the emitting regions in HD 54879.…”
Section: Discussioncontrasting
confidence: 54%
“…The atmospheric parameters presented by Castro et al (2015) suggest that HD 54879 has already slightly evolved from the ZAMS and is passing through the β Cephei instability strip. As mentioned above, Järvinen et al (2017) were not able to detect significant velocity shifts in high-resolution HARPSpol observations of HD 54879, most likely due to much longer exposure times, of the order of 1-3 h. During the long HARPSpol exposures, any spectral variability is smeared over the pulsation cycle and difficult to detect. In contrast, FORS 2 observations carried out using an 8 m telescope, have a duration of only 10-20 min and are expected to be more strongly affected by the β Cephei-like pulsations.…”
Section: Spectral Changes Accompanying the Sudden Increase Of The Mag...mentioning
confidence: 86%
“…As already reported by Järvinen et al (2017) Donati et al 2006) spectra with a spectral resolution of 65 000 obtained between 2014 November and 2018 January became publicly available in the CFHT archive. Among them, two observations were obtained on the same night on 2014 November 9.…”
Section: High-resolution Spectropolarimetry Of Hd 54879mentioning
confidence: 90%
“…The authors concluded that the dominant periodicity detected in TESS observations does not agree with constraints on the rotational period of HD 54879, hence some other mechanism must be responsible. Spectral variability on a short-time scale in HD 54879 was investigated by Järvinen et al (2017) using subexposures with different integration times in high-resolution HARPS spectropolarimetric observations. The analysis of these observations indicated distinct changes in line profiles belonging to different elements and taking place on timescales corresponding to the duration of the individual subexposures of the order of 15-45 min.…”
Section: Binaritymentioning
confidence: 99%
“…Since we have now more extensive spectroscopic material at our disposal, to test the presence of spectral variability on short time scales of the order of minutes, we used all available high-resolution ESPaDOnS spectropolarimetric observations, consisting each of four subexposures recorded with integration times between 8 and 15 min, which are even shorter than the subexposure integration times with HARPS. As Järvinen et al (2017) reported the strongest variationsof up to 0.5 per cent -in line profiles calculated from HARPS spectra using exclusively silicon lines, we compared the variability amplitude of the silicon lines with the variability of line profiles belonging to the elements oxygen and aluminium. The line mask for oxygen used in this test included fourteen O ii lines, that for Al four Al iii lines, and the silicon mask included five Si iii and two Si iv lines.…”
Section: Binaritymentioning
confidence: 99%